To regulate or not: A social dynamics analysis of an idealised ai race - Han, The Anh (2021)
PTDC/EEI-SII/5081/2014 PTDC/MAT/STA/3358/2014 UIDB/50021/2020 grant number 31257234 FLAG-ERA JCT 2016 FP2-154 UIDB/04516/2020